Macroeconomic variables influence towards property stock in Malaysia main market / Norsabrina Noorul Hisham - Noorul Hisham, Norsabrina (Faculty of Business Management, 2017)
The study of this research is to examine the relationship of property stock return and the macroeconomic factor. These factors are inteœst rate, inflation rate and money supply which known as macroeconomic variables. An ordinary least square (OLS) method will be using for this study as to obtain their relationship. The intention of this study is to provide a comprehension understanding to the investors and fund manager especially the property stockholders about performance of the property stock market and assist in providing some additional information about the property stocks in Malaysia. This study attempted to analyse the factors affecting the property stock excess return in Malaysia whereas it focuses on main market of Kuala Lumpur Stock Exchange. The fluctuation of the stock index may affects the level of property stock return. This may be due to the volatility of the property stock price in the market moves dramatically in which affecting the market performance. Volatility that is likely to increase may cause the stock market drops and reduces the returns thus, increases the risk. Hence, macroeconomic factor may reflect in the common business and financial stability. Several findings have attained from the results. Both of interest rate and inflation rate have a negative relationship with excess return. Meanwhile, money supply has a positive relationship with excess.